Judicial Politics and The Reconstruction of Indonesia’s Regional Head Election Design - Ida Budhiati; Unu Putra Herlambang (KRTHA BHAYANGKARA, 2026)
This article examines judicial politics in reconstructing Indonesia’s simultaneous regional head election design. The issue arises from the unstable constitutional position of regional head elections, which have moved between the regional government regime and the broader electoral regime. Using normative legal research with statutory, case, and conceptual approaches, this article analyses the 1945 Constitution, election and regional election laws, and Constitutional Court decisions, particularly Decisions No. 072-073/PUU-II/2004, 97/PUU-XI/2013, 55/PUU-XVII/2019, 85/PUU-XX/2022, and 135/PUU-XXII/2024. The article finds that the Constitutional Court has not merely acted as a negative legislator, but has also shaped constitutional parameters for electoral design through its jurisprudence. Decision No. 135/PUU-XXII/2024 represents a decisive shift by separating national elections from regional elections and positioning regional head elections within the architecture of regional elections. This reconstruction requires harmonisation between election and regional election laws, institutional strengthening of electoral bodies, and a tiered electoral justice system. The article contributes to constitutional election law by framing regional head election reform as a matter of judicially shaped democratic design.